1997
DOI: 10.1021/jp9705986
|View full text |Cite
|
Sign up to set email alerts
|

Directed Energy Transfer Funnels in Dendrimeric Antenna Supermolecules

Abstract: We have studied the dynamics of directed, multistep energy transport in a class of fractal-like dendrimeric molecules. For particular forms of these highly branched phenylacetylene dendrimers, both theory and experiment put the lowest excitation energy at the center (locus) of the supermolecule. This results in a structurally symmetric and ordered exciton funnel, with a well-directed energy gradient. We have designed and synthesized a derivative of these dendrimers with a perylene moiety at the locus, which ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
253
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(259 citation statements)
references
References 25 publications
4
253
0
2
Order By: Relevance
“…[8][9][10][11][12][13] Since they can be prepared with high regularity and controlled molecular weights, 14 dendrimers offer great promise in the control of energy funneling. Their successful directional-energy transfer has been studied by Moore et al, 15,16,9,17 who have reported the syntheses of a peryleneterminated dendrimer, called the nanostar. This molecule presents four generations of linear PPE segments with decreasing lengths toward the periphery, creating an efficient energy funnel toward the perylene trap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Since they can be prepared with high regularity and controlled molecular weights, 14 dendrimers offer great promise in the control of energy funneling. Their successful directional-energy transfer has been studied by Moore et al, 15,16,9,17 who have reported the syntheses of a peryleneterminated dendrimer, called the nanostar. This molecule presents four generations of linear PPE segments with decreasing lengths toward the periphery, creating an efficient energy funnel toward the perylene trap.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the excitons in the nanostar are localized on each PPE segment, 9 and its overall absorption spectrum can be interpreted as the sum of these individual contributions. 15,10,17 Theoretical interest in PPE dendrimers arises from the possibility of analyzing them as an ensemble of individual coupled chromophore units. Therefore, the system can be described using the Frenkel exciton Hamiltonian 18,19 with Coulombic coupling between excitations localized on the linear units.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Rather than employing a linear geometry like in polymers, dendrimers are based on a self-similar fractal branching geometry, where the amount of branching increases with the size of the molecule. Through elegant synthetic routes it has been possible to create large, almost nanoscale molecules with a wide range of functional properties ranging from molecular recognition, such as in drug delivery systems 1 to artificial light-harvesting antennae.…”
mentioning
confidence: 99%
“…Through elegant synthetic routes it has been possible to create large, almost nanoscale molecules with a wide range of functional properties ranging from molecular recognition, such as in drug delivery systems 1 to artificial light-harvesting antennae. 3,4,9 A particularly interesting area of applications is in optoelectronic devices such as light-emitting diodes ͑LEDs͒, where dendrimers have been used both as emitting layers 6,7,10 and as charge transport layers. 11,12 The well defined chemical structure of dendrimers allows a systematic correlation to be drawn between the device properties and the dendrimer structure.…”
mentioning
confidence: 99%
“…Striking examples of this principle can be seen in classic work on perylene-functionalised phenylacetylene dendrimers [35,36]. An example of a organosilicon cationic dendrimer is given in figure 6.…”
Section: Dendrimersmentioning
confidence: 93%